Vitrectomy combined with lens capsule flap transplantation in the treatment of high myopia macular hole retinal detachment: study protocol for a prospective randomised controlled trial - Xun Xu; Tianwei Qian; Hao Zhou; Weijun Wang; Ying Fan; Lin Xue; Xia Wu; Qiaoyun Gong; Luyao Ye (BMJ Open)
Introduction Vitrectomy combined with internal limiting membrane (ILM) peeling, flap or tamponade is widely used in the treatment of macular diseases, such as macular hole (MH) and high myopia macular hole retinal detachment (HMMHRD). However, movement of the ILM to a suitable position to prevent displacement is a difficult operation. Improving visual function after surgery remains controversial. Compared with ILM, the thicker and more flexible lens capsule is easy to obtain and operate. Previous studies have confirmed the effectiveness of lens capsule flap in the treatment of MH. This study aims to evaluate the efficacy and safety of vitrectomy combined with lens capsule flap transplantation in the treatment of HMMHRD.Methods and analysis This single-centre, single-blind, prospective, randomised clinical trial will include 54 patients with HMMHRD who will first undergo phacoemulsification and intraocular lens implantation and then vitrectomy combined with lens capsule flap transplantation (experimental group) or ILM tamponade (control group). Study participants will be randomly allocated in a 1:1 ratio to experimental and control groups. Follow-up will be conducted 1, 3 and 7 days and 1, 3 and 6 months after surgery in both groups. Necessary examinations will be performed at each follow-up visit. Measurement outcomes include postoperative situation of macular hole closure, best-corrected visual acuity, macular retinal function and macular retinal sensitivity. The primary outcome is type I closure rate of MH 6 months after operation. Intergroup comparisons of the proportions of patients with type I closure of MH will be performed with Fisher’s exact test.Ethics and dissemination Full ethics approval for this study was obtained from the Ethics Committee of Shanghai General Hospital, Shanghai Jiaotong University, Shanghai, China. The outcomes of the trial will be disseminated through peer-reviewed journals and at scientific conferences.Trial registration number ChiCTR2200057836.